Small heat shock protein 20 interacts with protein phosphatase-1 and enhances sarcoplasmic reticulum calcium cycling - Qian, J.; Vafiadaki, E.; Florea, S. M.; Singh, V. P.; Song, W.; Lam, C. K.; Wang, Y.; Yuan, Q.; Pritchard, T. J.; Cai, W.; Haghighi, K.; Rodriguez, P.; et al. (Circ ResCirc ResCirc Res, 2011)
BACKGROUND: Heat shock proteins (Hsp) are known to enhance cell survival under various stress conditions. In the heart, the small Hsp20 has emerged as a key mediator of protection against apoptosis, remodeling, and ischemia/reperfusion injury. Moreover, Hsp20 has been implicated in modulation of cardiac contractility ex vivo. The objective of this study was to determine the in vivo role of Hsp20 in the heart and the mechanisms underlying its regulatory effects in calcium (Ca) cycling. METHODS AND RESULTS: Hsp20 overexpression in intact animals resulted in significant enhancement of cardiac function, coupled with augmented Ca cycling and sarcoplasmic reticulum Ca load in isolated cardiomyocytes. This was associated with specific increases in phosphorylation of phospholamban (PLN) at both Ser16 and Thr17, relieving its inhibition of the apparent Ca affinity of SERCA2a. Accordingly, the inotropic effects of Hsp20 were abrogated in cardiomyocytes expressing nonphosphorylatable PLN (S16A/T17A). Interestingly, the activity of type 1 protein phosphatase (PP1), a known regulator of PLN signaling, was significantly reduced by Hsp20 overexpression, suggesting that the Hsp20 stimulatory effects are partially mediated through the PP1-PLN axis. This hypothesis was supported by cell fractionation, coimmunoprecipitation, and coimmunolocalization studies, which revealed an association between Hsp20, PP1, and PLN. Furthermore, recombinant protein studies confirmed a physical interaction between AA 73 to 160 in Hsp20 and AA 163 to 330 in PP1. CONCLUSIONS: Hsp20 is a novel regulator of sarcoplasmic reticulum Ca cycling by targeting the PP1-PLN axis. These findings, coupled with the well-recognized cardioprotective role of Hsp20, suggest a dual benefit of targeting Hsp20 in heart disease.
Keywords: *Myocardial Contraction; Amino Acid Substitution; Animals; Calcium-Binding Proteins/genetics/metabolism; Calcium/*metabolism; Heart Diseases/genetics/metabolism; HSP20 Heat-Shock Proteins/*biosynthesis/genetics; Mice; Mice, Transgenic; Mutation, Missense; Myocardium/*metabolism; Phosphorylation/genetics; Protein Phosphatase 1/genetics/*metabolism; Sarcoplasmic Reticulum Calcium-Transporting ATPases/genetics/metabolism; Sarcoplasmic Reticulum/genetics/*metabolism